Accounting for acquired goodwill in Australian business combinations: is there value to choose? - James, Kieran E. (Curtin University, 2005)
This research explores the empirical association between takeover bid premium and acquired goodwill, and tests whether the empirical association changes after the passage of approved accounting standard AASB1013: Accounting for Goodwill. AASB1013 mandates capitalization and amortization of acquired goodwill to the profit and loss account, over a maximum time period of 20 years. Using real options and contracting cost frameworks, this study argues that reducing the variety of accounting policy options available to bidder management after an acquisition results in a systematic loss in firm value. An empirical model developed by Robinson and Shane (1990) and Choi and Lee (1991) is used to measure the average effect on bid premiums of the mandatory change in accounting rule, after controlling for a range of confounding variables including mode of payment, managerial share ownership, and bidder prior share ownership. Based on a final sample consisting of 127 pre-AASB1013 bids and 134 post-AASB1013 bids, the results show that the goodwill accounting rule contained in AASB1013 significantly reduces both the mean and median level of bid premium and the strength of the association between acquired goodwill and bid premium.